Extending Decomposition Analysis to Account for Socioeconomic Background: Income-Related Smoking Inequality among Swedish Women - Gustav Kjellsson (Lund University, School of Economics and Management, Department of Economics, 2014)
This article suggests an extension of the standard decomposition of the concentration index that allows for an exploration of the pathways through which socioeconomic background relates to income-related health inequality. This novel approach is contrasted to the standard one using a panel of Swedish women in Statistics Sweden's Survey of Living Conditions for one vital health-related behavior, smoking. The decomposition uses an underlying model that considers both individual heterogeneity and smoking persistence, showing that the largest contributions to the pro-rich smoking inequality come from years of schooling and living in a single household. The contribution from socioeconomic background is close to negligible when using the standard approach. Once applying the suggested extension, socioeconomic background contributes indirectly to the inequality, primarily through an increase in years of schooling. These results highlight the potential importance of using this extension, especially for distinguishing between circumstances that individuals may affect themselves and these that are out of their control, which may be important for policy design.
Keywords: I12; I14; 330; Health inequality; concentration index; decomposition; smoking; socioeconomic background